Ngethrift Business Model Development - Dessy Aliandrina; Fadia Janita Rahma (ConCEPt - Conference on Community Engagement Project, 2023)
Buying and wearing used clothes is still considered taboo and embarrassing by many people in Indonesia. However, a new phenomenon has emerged, namely the current thrifting trend. Thrifting means hunting for used clothes. Thrifting activities aim to support the sustainable fashion movement that emphasizes environmental and human values. Thrifting motivation is driven by the desire to save money, look unique and different, and care about the environment. Thrifting in society is not just a dress activity but also a desire to take part in saving the earth and reducing waste. The concept of Ngethrift's business is to reuse clothes that are no longer used to become something of value, by reselling or donating to those who need it more so that it has business value and social value. This business is a place to accommodate used clothes from the community which will then be distributed to be donated or modified into something that can be a selling point. Ngethrift is a thrifting business located in Sambas which sells it offline and has not yet started doing online-based business. Ngethrift currently needs to make a breakthrough to survive in today's digital era.